2023
DOI: 10.1080/07391102.2023.2192797
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing immune boosting and anti-viral efficacy of Parkia bioactive entities as multi-target directed therapeutic approach for SARS-CoV-2: exploration of lead drugs by drug likeness, molecular docking and molecular dynamics simulation methods

Abstract: Root P. speciosa † Instability index < 40 and > 40 is predicted the protein as stable and unstable, respectively. ‡ Aliphatic index (alanine, valine, isoleucine, and leucine) is regarded as a positive factor for the increase of thermostability of globular proteins.$ GRAVY is calculated as the sum of hydropathy values of all the amino acids, divided by the number of residues in the sequence. Negative and positive GRAVY values indicate that the protein is non-polar and polar, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…Previous biochemical and in silico studies have revealed that some NPs, including bile acids like tauro-α-muricholic acid 20 , 25 , β-amyrin 40 , folic acid 41 , vitamin B6 42 , campesterol and stigmasterol 43 can bind to R1, R2, or at the interface of R1–R2 interfering with the interactions between the RBD and the ACE2 receptor. These natural products thus, are proposed to have therapeutic benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Previous biochemical and in silico studies have revealed that some NPs, including bile acids like tauro-α-muricholic acid 20 , 25 , β-amyrin 40 , folic acid 41 , vitamin B6 42 , campesterol and stigmasterol 43 can bind to R1, R2, or at the interface of R1–R2 interfering with the interactions between the RBD and the ACE2 receptor. These natural products thus, are proposed to have therapeutic benefits.…”
Section: Resultsmentioning
confidence: 99%
“…CARM1 inhibition was shown to limit H3R17 methylation, resulting in decreased H3K9 acetylation and HDAC9 dissociation [268]. Ellagic acid and other plant-derived substances strongly bound with the multiple targets of the SARS-CoV-2 receptors, inhibiting viral entry, attachment, binding, replication, transcription, maturation, packaging, and spread [269]. Curcumin is known to strongly stop the production of several proinflammatory cytokines that cause the "cytokine storm" that occurs in some viral infections.…”
Section: Ellagic Acidmentioning
confidence: 99%
“…Decreases H3K9 acetylation and HDAC9 dissociation [268]. Inhibits SARS-CoV-2 viral entry and replication [269].…”
Section: Ellagic Acidmentioning
confidence: 99%
See 1 more Smart Citation